1995
DOI: 10.1111/j.1471-6402.1995.tb00276.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Analysis Of The Relationships Among Sexual Assault Experiences: An Extension of Previous Findings

Abstract: Research has indicated that sexual assault on college campuses is pervasive (Koss, Gidycz, & Wisniewski, 1987) and that a history of sexual victimization serves as a risk factor for future victimization (Gidycz, Coble, Latham, & Layman, 1993). The purpose of the present investigation was to extend the findings of Gidycz et al. (1993) in examining the link among sexual victimization experiences. College women were evaluated for child and adolescent sexual victimization, family adjustment, alcohol use, psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
281
8
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 273 publications
(324 citation statements)
references
References 40 publications
31
281
8
4
Order By: Relevance
“…This scale possesses strong convergent validity with interview measures [32]. In regard to severity, previous research has classified participants who endorse only acts of exposure and/or touching during childhood as moderate, while threatened or completed intercourse has been classified as severe [31].…”
Section: Childhood Sexual Abuse Questionnaire (Csaq)mentioning
confidence: 99%
See 1 more Smart Citation
“…This scale possesses strong convergent validity with interview measures [32]. In regard to severity, previous research has classified participants who endorse only acts of exposure and/or touching during childhood as moderate, while threatened or completed intercourse has been classified as severe [31].…”
Section: Childhood Sexual Abuse Questionnaire (Csaq)mentioning
confidence: 99%
“…The SES was used to assess for SAH occurring at 14 years or older. Previous research has proposed severity cut-offs for this scale, dividing types of assaults into moderate and severe categories [31]. Moderate events in adulthood included pressured or forced fondling, kissing, or petting (but not intercourse), as well as intercourse that results from coercion, but not physical force.…”
Section: Sexual Experience Survey (Ses)mentioning
confidence: 99%
“…A meta-analysis conducted by Roodman and Clumb (2001) suggests a significant positive relationship between childhood victimization and adult victimization experiences. Gidycz et al (1995) further suggested a significant positive relationship between the severity of past sexual abuse and an increased risk of future victimization.…”
Section: Victimsmentioning
confidence: 99%
“…In a follow-up study, Gidycz, Hanson, and Layman (1995) used the same design as Gidycz et al (1993) to investigate the relationship between one's experiences of sexual aggression and the mediating effects of psychological adjustment. In this study, the mediating factors were expanded to include interpersonal functioning, alcohol use, family functioning, and sexual behaviours.…”
Section: Victimsmentioning
confidence: 99%
See 1 more Smart Citation